Artificial Intelligence (AI) Chatbots and Critical Thinking: Gen Z's Perspective on Completing Tasks in the Era of Society 5.0. - Sony Zulfikasari; Basuki Sulistio; Niam Wahzudik (Indonesian Journal of Educational Science (IJES), 2025)
Critical thinking plays a crucial role in the academic and professional development of students. The integration of artificial intelligence (AI) in the context of Society 5.0 is particularly noteworthy, especially with the emergence of AI Chatbot tools that are transforming how students engage in learning. This study aims to explore students' perceptions of using chatbots concerning their critical thinking abilities when completing assignments. To achieve this, a descriptive quantitative research method was employed, utilizing survey questionnaires distributed to students. The analysis involved collecting, structuring, and interpreting quantitative descriptive data, with instrument validity ensured through expert review. The results indicate that Chatbot AI can support Gen Z students in developing critical thinking skills by helping them clarify problems, categorize information, and structure their answers. However, it should not replace the importance of discussion and reflection. Therefore, its use should be balanced with learning strategies that promote information verification, academic discussions, and practical application. Educational institutions must ensure that chatbot AI usage fosters reflection, provides contextualized solutions, and encourages ethical practices.